Cell-size-dependent upregulation of HGF expression in dermal fibroblasts: Impact on human skin connective tissue aging. Issue 3 (December 2017) - Qin, Zhaoping; Worthen, Christal A.; Quan, Taihao
Highlights: As HGF suppresses collagen production, its role in human connective tissue aging is unknown. HGF is significantly elevated in aged human skin dermis in vivo . Reduced fibroblast size, which is a prominent feature of aged skin fibroblasts in vivo, is responsible for elevated HGF expression. Cell-size-dependent upregulation of HGF expression is driven by increased c-Jun and impaired TGF-β signaling. Suppression of HGF may benefit for aged human skin by improving collagen production. Abstract: Background: Aged human skin is primarily attributable to loss of collagen, the main structural component of skin. Hepatocyte growth factor (HGF) acts as an anti-fibrotic factor by suppression of collagen production. It is not known whether HGF is involved in age-related collagen deficit in human skin. Objective: The objective of this study was to investigate the expression of HGF in human skin, and the underlying mechanisms of age-related elevation of HGF expression. Methods: The expression of HGF in young (25 ± 5 years, six subjects) and aged (75 ± 6 years, six subjects) human skin was determined by laser capture microdissection (LCM) coupled real-time PCR and immunohistology. The underlying mechanisms of age-related elevation of HGF were investigated by reducing dermal fibroblast size, which is a prominent feature of aged skin fibroblast in vivo . Results: HGF is predominantly expressed in human skin dermal fibroblasts, the major cells responsible for collagen production, and is significantly elevated in aged human skin in vivo . Mechanistically, reduced fibroblast size, which is a prominent feature of aged skin fibroblasts in vivo, is responsible for age-related elevation of HGF expression. Cell-size-dependent upregulation of HGF expression is driven by increased c-Jun and impaired TGF-β signaling. Restoration of fibroblast size normalizes increased c-Jun expression and impaired TGF-β signaling, and thus reversed the elevated HGF expression. Finally, we confirmed that application of retinoid (ROL), which has been shown to improve aged human skin, significantly reduced elevated HGF mRNA expression in aged human skin in vivo (78 ± 4 years, six subjects). Conclusion: These data reveal a novel mechanism by which reduction of fibroblast size upregulates HGF expression, which in turn contributes to loss of collagen, a prominent feature of aged skin.